A Trainee’s Approach for Effective Operating Room Learning - Hassan Tahir; Madiha Haroon; Usman Ali Mobin; Faisal Siddiqi; Mirza Arshad Beg (European Scientific Journal, ESJ, 2021)
Introduction: Surgical training has gone through a paradigm shift in recent years. The trends have shifted from an apprenticeship model to a new era of self-teaching and an attitude-driven learning. In this study, we aim to comprehensively investigate the knowledge and attitude pertaining to the perception of preparation required for the operating room and how the residents prepare themselves for it. Method: A quantitative study was conducted via predefined questionnaire. Surgical residents at a single tertiary care institution were asked to complete the survey via Google forms that was distributed by means of email to residents of the general surgery department. Inclusion and exclusion criteria were defined. Results: Forty surgical residents opted to participate in the survey. The majority of the residents had a similar perception of operating room preparation. The most prominent theme that emerged following the discussion was that the residents learned through trial and error, and advice solicited from co-residents, which in the majority of the cases, were senior level resident. The resources defined by the residents were similar among majority and factors that affected their preparation were variable. An important aspect highlighted through the discussion was that the level of postgraduate training affected the preparation done by residents in order to better perform in operation theatres. Conclusion: Knowledge and attitude regarding operating room preparation was quite similar among the surgical residents. They varied in their practice for preparation.